Freedom is not free : if we are not part of the solution, then we are the problem - Khera, Shiv. (New Delhi : Bloomsbury, 2014)
This book was a result of the author's anguish and refusal to tolerate injustice, corruption and oppression any further. It is his call to his countrymen to stand up and fight for principles and help in reforming society.
Keywords: Political participation